Identification of Ornamental Plants Via Google Lens Based on Intersemiotic - Nuraini Nuraini; Allif Syahputra Bania; Najihatul Faridy; Nursamsu Nursamsu (Postgraduate, University of Mataram, 2022)
This research aims to develop a feasibility test and practical application of biology learning media technology, especially in terms of taxonomy introduction via google lens. The experimental method was used to collect identification data regarding intersemiotic translation of ornamental plants. The stage to find out the quality of intersemiotic translation of the research object using a google lens in the form of the general method of photo analysis in the use of google lens using the keys of google lens results evaluation method by Shapovalov et al. (2020). The research object which was taken randomly via google lens will be analyzed for information regarding three to six detected results to examine information about the object based on genus and species. The result is google lens can identify ornamental plants well. Intersemiotic translation results have been obtained in the seven plants as research objects. Five research objects have a score of 3 and two research objects get a score of 2 based on the keys of google lens results evaluation. The identification of ornamental plants from the photo is Aglaonema plant, Tillandsia Usneoides, Sansevieria Trifasciata, Aechmea chantinii, Neoregelia fireball, Neoregelia marmorata, and Calathea Makoyana